2015
DOI: 10.1900/rds.2015.12.299
|View full text |Cite
|
Sign up to set email alerts
|

Complex Genetics of Type 2 Diabetes and Effect Size: What have We Learned from Isolated Populations?

Abstract: ■ AbstractGenetic studies in large outbred populations have documented a complex, highly polygenic basis for type 2 diabetes (T2D). Most of the variants currently known to be associated with T2D risk have been identified in large studies that included tens of thousands of individuals who are representative of a single major ethnic group such as European, Asian, or African. However, most of these variants have only modest effects on the risk for T2D; identification of definitive 'causal variant' or 'causative l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 130 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…From an evolutionary perspective, rare variants are on average more recent than common variants, and are thus more likely to be disease risk factors. Genetic association studies of common diseases and traits in isolated populations were particularly advantageous for identification of risk loci that are rare in the general population, but possibly enriched or common in an isolated population (Trecartin et al 1981;Baier and L.Hanson 2004;Kristiansson et al 2008;Sabatti et al 2009;Zeggini 2014;Nair and Baier 2015;Fang et al 2016;Gilly et al 2016;Lopes et al 2016;Zeggini et al 2016). The Ashkenazi Jewish (AJ) population has been an attractive population for genetic studies, because of its unique demographic history of a recent severe bottleneck followed by a rapid expansion and monogamy (Guha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary perspective, rare variants are on average more recent than common variants, and are thus more likely to be disease risk factors. Genetic association studies of common diseases and traits in isolated populations were particularly advantageous for identification of risk loci that are rare in the general population, but possibly enriched or common in an isolated population (Trecartin et al 1981;Baier and L.Hanson 2004;Kristiansson et al 2008;Sabatti et al 2009;Zeggini 2014;Nair and Baier 2015;Fang et al 2016;Gilly et al 2016;Lopes et al 2016;Zeggini et al 2016). The Ashkenazi Jewish (AJ) population has been an attractive population for genetic studies, because of its unique demographic history of a recent severe bottleneck followed by a rapid expansion and monogamy (Guha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide analysis studies focused specifically on the Mexican and Mexican American populations identified a candidate locus that could result in disordered lipid metabolism; this locus occurs at high frequency in Native American and East Asian populations but is rare in Caucasians [17]. Other work from the Pima Indian populationnearly 50% of whom have diabetesidentified a locus that predisposes to high birthweight and confers a twofold increase in the risk for type 2 diabetes [18]. A recent study comparing insulin profiles in two high-risk ethnic groups found a higher propensity for insulin resistance, as measured by HOMA-IR, among Pima Indians compared with Asian Indians, who had substantially lower insulin secretion [19].…”
Section: Risk Factors For Cvd: Why We Need Studies In Diverse Populatmentioning
confidence: 99%
“…A number of different genetic variants, but risk is small (small effect size with odds ratio of <1.5), have been identified as risk factors for an individual's susceptibility for T2D development. However, these risk factors, alone or in combination may have the potential to substantially affect the clinical picture and cure of T2D patients 56‐63 …”
Section: Diabetes Mellitusmentioning
confidence: 99%